Relevance of Test- and Subject-Related Factors on Inhibitory Avoidance (Performance) of Zebrafish for Psychopharmacology Studies - Manuel, Remy; Gorissen, Marnix; van den Bos, Ruud (Current Psychopharmacology, 2016)
Background: The inhibitory (or passive) avoidance paradigm is widely used to assess the effects of drugs on emotion, learning and memory in rodents. The zebrafish is gaining more and more popularity as an animal model in, among others, psychopharmacological research. In zebrafish, inhibitory avoidance is also used as assay to assess the effects of drugs and other treatments on fear-associated learning. The inhibitory avoidance paradigm is based on the conflict between (i) the innate response to enter a dark area to avoid a brightly lit area (scototaxis) and (ii) avoiding exposure to a shock in the dark area, i.e. contextual (shock-environment) fear-learning. Objective: This review summarises recent studies that characterised different features of the inhibitory avoidance paradigm. This knowledge is necessary to fully appreciate drug-related effects in this task. Results: These studies have revealed factors that affect performance of zebrafish in the task, e.g. test-related parameters (such as shock intensity) and subject-characteristics at the time of testing (including age, strain and rearing conditions). In addition, they allowed generating hypotheses on physiological and genetic mechanisms underlying inhibitory avoidance in zebrafish. Conclusion: The inhibitory avoidance assay is a useful research tool to study emotion, learning and memory in zebrafish. Directions for future research are indicated, which may further optimise the use of the inhibitory avoidance assay in zebrafish as research tool.
Keywords: genetics